BIOCONTROL POTENTIAL OF MIXTURE OF TRICHODERMA ISOLATES ON DAMPING-OFF AND COLLAR ROT OF TOMATO - S. P. SINGH; H. B. SINGH; D. K. SINGH (The Bioscan, 2014)
Sclerotium rolfsii is a notorious phytopathogen causing serious damage to a wide variety of hosts. Management of this pathogen requires large inputs of chemical pesticides to treat the affected soil which leads to environmental pollution. Two Trichoderma isolates BHU51 and BHU105 were tested singly and in combination for their biocontrol potential against S. rolfsii under glass house and field conditions. All Trichoderma treatments significantly reduced the damping-off severity in tomato which was observed up to 30 days after sowing (DAS). In consortium of Trichoderma (BHU51+BHU105) incidence of damping-off was recorded only 22% while in control it was found 54.67%. Highest shoot length (15.16 cm), root length (3.56 cm) and their respective fresh weight (887.53 mg and 47.33 mg) and dry weight (54.27 mg and 4.45 mg) also found highest in the mixture of Trichoderama treatment followed by single Trichoderma treatments while the lowest was recorded in the control in glass house conditions. Highest vigor index (1301.67) was recorded in the mixture of Trichoderma treatment while the lowest (465.67) was found in control. The minimum mean disease rating (1.71 and 1.96), maximum percent disease reduction (42.85 and 44.32) and highest shoot length, chlorophyll content and yield was recorded in the consortium of Trichoderma in field experiments in both the years. The results indicated that a consortium of compatible Trichoderma isolates can lead to greater protection and ultimately greater yield over single Trichoderma isolate.